ESG DIMENSIONS AND CORPORATE PERFORMANCE – FINANCIAL SLACK AS A MODERATING VARIABLE: EVIDENCE FROM EMERGING MARKETS - Aulia Rayendra Rahman; Nur Dhani Hendranastiti (RADJA PUBLIKA, 2025)
This paper analyzes the effects of Environmental, Social, and Governance (ESG) factors, including their three pillars and ESG controversies, on corporate performance in environmentally sensitive industries across ASEAN countries. ESG issues have gained prominence due to their association with environmental degradation, labor exploitation, and lack of transparency, all of which pose risks to corporate sustainability. In emerging markets, the implementation of ESG practices faces challenges such as inadequate infrastructure and financial limitations, which may hinder companies from adopting sustainable practices and improving performance. This study addresses these challenges by introducing financial slack as a moderating variable, aiming to determine if financial flexibility impacts the relationship between ESG engagement and corporate performance, assessed through Return on Equity (ROE), Return on Assets (ROA), and Tobin's Q. Utilizing panel data from 2019 to 2023 and applying moderated regression analysis reveals that ESG engagement and its pillars are negatively linked to corporate performance. Furthermore, financial slack mitigates the negative outcome of overall ESG engagement, along with the Environmental and Governance pillars, on these performance indicators. These findings highlight the importance of financial flexibility in supporting ESG implementation in emerging economies and environmentally sensitive industries.